Temporal discrimination threshold: VBM evidence for an endophenotype in adult onset primary torsion dystonia. - Reilly, Richard; Whelan, Robert; Walsh, Richard; Hutchinson, Siobhan; Bradley, David (My University, 2009)
Familial adult-onset primary torsion dystonia is an autosomal dominant disorder with markedly reduced penetrance. Most adult-onset primary torsion dystonia patients are sporadic cases. Disordered sensory processing is found in adult-onset primary torsion dystonia patients; if also present in their unaffected relatives this abnormality may indicate non-manifesting gene carriage. Temporal discrimination thresholds (TDTs) are abnormal in adult-onset primary torsion dystonia, but their utility as a possible endophenotype has not been examined. We examined 35 adult-onset primary torsion dystonia patients (17 familial, 18 sporadic), 42 unaffected first-degree relatives of both familial and sporadic adult-onset primary torsion dystonia patients, 32 unaffected second-degree relatives of familial adult-onset primary torsion dystonia (AOPTD) patients and 43 control subjects. TDT was measured using visual and tactile stimuli. In 33 unaffected relatives, voxel-based morphometry was used to compare putaminal volumes between relatives with abnormal and normal TDTs. The mean TDT in 26 control subjects under 50 years of age was 22.85 ms (SD 8.00; 95% CI: 19.62-26.09 ms). The mean TDT in 17 control subjects over 50 years was 30.87 ms (SD 5.48; 95% CI: 28.05-33.69 ms). The upper limit of normal, defined as control mean + 2.5 SD, was 42.86 ms in the under 50 years group and 44.58 ms in the over 50 years group. Thirty out of thirty-five (86%) AOPTD patients had abnormal TDTs with similar frequencies of abnormalities in sporadic and familial patients. Twenty-two out of forty-two (52%) unaffected first-degree relatives had abnormal TDTs with similar frequencies in relatives of sporadic and familial AOPTD patients. Abnormal TDTs were found in 16/32 (50%) of second-degree relatives. Voxel-based morphometry analysis comparing 13 unaffected relatives with abnormal TDTs and 20 with normal TDTs demonstrated a bilateral increase in putaminal grey matter in unaffected relatives with abnormal TDTs. The prevalence of abnormal TDTs in sporadic and familial AOPTD patients and their first-degree relatives follows the rules for a useful endophenotype. A structural correlate of abnormal TDTs in unaffected first-degree relatives was demonstrated using voxel-based morphometry. Voxel-based morphometry findings indicate that putaminal enlargement in AOPTD is a primary phenomenon. TDTs may be an effective tool in AOPTD research with particular relevance to genetic studies of the disorder.
PUBLISHED
Keywords: Psychiatry; endophenotype; dystonia; temporal discrimination; voxel-based morphometry; putamen; Neuroscience; Next Generation Medical Devices